Symplocamide A, a Potent Cytotoxin and Chymotrypsin Inhibitor from the Marine Cyanobacterium Symploca sp - Linington, Roger G. (2007)
Investigation of a Symploca sp. from Papua New Guinea has led to the isolation of symplocamide A (1), a potent cancer cell cytotoxin, which also inhibits serine proteases with a 200-fold greater inhibition of chymotrypsin over trypsin. The complete stereostructure of symplocamide A was determined by detailed NMR and MS analysis as well as chiral HPLC analysis of the component amino acid residues. The presence of several unusual structural features in symplocamide A provides new insights into the pharmacophore model for protease selectivity in this drug class and may underlie the potent cytotoxicity of this compound to H-460 lung cancer cells (IC(50) = 40 nM) as well as neuro-2a neuroblastoma cells (IC(50) = 29 nM).